Can bribery buy health? Evidence from post-communist countries - Astghik Mavisakalyan; Vladimir Otrachshenko; Olga Popova (Global Labor Organization (GLO), 2019)
Corruption is pervasive, but we know little about its effects on individual lives. This paper examines whether living in a corrupt society has deleterious effects on health. Using individual-level data from 28 post-communist countries, we demonstrate that bribing for public services worsens self-assessed health. Unlike other studies, we account for endogeneity of bribery and show that bribing for any type of public service, not just for health services, has an adverse impact. We also find that bribery lowers the quality of services received. Moreover, there are potentially high indirect costs of bribery since, as we show, it comes at the expense of cutting food consumption. These findings suggest that corruption is a potentially important source behind the poor health outcomes in many developing countries.
Keywords: I15; K42; D73; H11; 330; Bribery; Corruption; Health; Post-Communist Countries